Mechanism of Synsepalum dulcificum Daniell. Inhibiting Lung Adenocarcinoma. (12th February 2022) - Chen, Qi; Liu, Tingting; Bai, Tuya; Zhang, Mengdi; Hu, Yuxia; Li, Jun; Chang, Fuhou
Abstract : Objective : Synsepalum dulcificum Daniell. (SD) is a natural plant fruit and is famous for containing miraculin. It has been reported that SD can be used as an adjuvant treatment to correct patients' loss of taste during the antitumor process, but the effect of SD itself as an antitumor is not clear. In this study, we investigated the mechanism of action of SD on lung adenocarcinoma using network pharmacology. Materials and Methods . The components of SD were identified by liquid chromatography-mass spectrometry, and then the compounds that affect tumor immunity of SD were screened and the related targets were predicted by TCMIO database. At the same time, the results were associated with lung adenocarcinoma targets included in the MalaCards and CTD databases, so as to construct a compound-target action network diagram and explore the mechanism of SD in the treatment of lung adenocarcinoma. In in vitro experiments, cell viability was determined and western blotting was used to detect the related expression of action targets to determine the therapeutic effect of SD. Results . In this experiment, 335 chemical components were identified in SD, and 107 components were related to tumor immunity. After screening by ADME, it was found that 11 compounds might be inhaled into the human body and affect the growth of lung adenocarcinoma. In vitro experiments showed that SD could inhibit the growth of lung adenocarcinoma A549 cells. SD could reduce the expression of PCNA (P < 0.05 ) and significantly increase the expression of Caspase-3 (P < 0.05 ). The results of further experiments showed that SD could significantly reduce the phosphorylation of EGFR (P < 0.05 ), and SD could also effectively inhibit the expression of JAK and STAT3 phosphorylation (P < 0.01 ) and inhibit the expression of PI3K and AKT phosphorylation (P < 0.01 ). Conclusion . SD can inhibit the growth of lung adenocarcinoma A549 cells and the potential mechanism was found to be the inhibition of EGFR/JAK/STAT3 and EGFR/PI3K/AKT signaling pathway, and the substance basis for SD to exert antitumor effect may be catechin, taxifolin, betaine, epigallocatechin gallate, erucamide, guanosine, kaempferol, lanosterol, morin, oleanolic acid, and quercetin.